2007
DOI: 10.1016/j.bbapap.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight protein tyrosine phosphatase (LMW-PTP) and its possible physiological functions of redox signaling in the eye lens

Abstract: Low molecular weight protein tyrosine phosphatase (LMW-PTP) was cloned from human lens epithelial B3 cells (HLE B3) and the recombinant enzyme was purified to homogeneity. The pure enzyme reacted positively with anti-LMW-PTP antibody, displayed tyrosine-specific phosphatase activity and was extremely sensitive to H 2 O 2 . The inactivated LMW-PTP could be regenerated by thioltransferase (TTase)/GSH system as demonstrated by both activity assay and by mass spectrometry (MS). The MS study also showed that an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Our results showed that knocking down TXNIP expression blunted VEGF-induced S-glutathionylation of LMW-PTP resulting in its hyperactivation and inhibition of VEGFR2. In support, LMW-PTP activity has been shown to be regulated by the glutathione reducing system and cellular redox state (9,53). involvement of PTP1B or SHP1 in TXNIP-mediated regulation of VEGFR2 activation (40), future work is warranted to examine whether S-glutathionylation can play a role in modulating other phosphatases similar to LMW-PTP.…”
mentioning
confidence: 97%
“…Our results showed that knocking down TXNIP expression blunted VEGF-induced S-glutathionylation of LMW-PTP resulting in its hyperactivation and inhibition of VEGFR2. In support, LMW-PTP activity has been shown to be regulated by the glutathione reducing system and cellular redox state (9,53). involvement of PTP1B or SHP1 in TXNIP-mediated regulation of VEGFR2 activation (40), future work is warranted to examine whether S-glutathionylation can play a role in modulating other phosphatases similar to LMW-PTP.…”
mentioning
confidence: 97%
“…In parallel, VEGF induced the immediate yet reversible thiol oxidation of LMW-PTP (1-5 minutes), which was restored to normal levels after 15 minutes. The activity of LMW-PTP is dually regulated, whereby the two active cysteines (C13 and C18) that are located in the catalytic pocket must be reduced to allow enzyme phosphorylation and activity (Chiarugi, 2001;Chiarugi et al, 2001;Xing et al, 2007). In agreement, VEGF-induced phosphorylation of LMW-PTP was detected only after 15-30 minutes, a time frame where thiols of LMW-PTP are not oxidized.…”
Section: Discussionmentioning
confidence: 81%
“…LMW-PTP shares the CX5R motif with other protein tyrosine phosphatases (PTPs), which render them vulnerable targets for cellular redox changes (Okamoto et al, 2001;Shackelford et al, 2005;Shelton and Mieyal, 2008). Furthermore, a unique property of LMW-PTP is that it has two cysteines that are located in the catalytic pocket; both cysteines must be reduced for enzyme phosphorylation and activity (Chiarugi, 2001;Chiarugi et al, 2001;Xing et al, 2007). Therefore, the activity of LMW-PTP is tightly linked to redox-changes and can be a molecular switch for the regulation of cell migration and angiogenesis (Giannoni et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…27 TTase is also known to be a multifunctional enzyme with a role in many biochemical processes, including protein dethiolation, 29 reduction of ribonucleotide reductase, 28,30 reactivation of key glycolytic and oxidation defense enzymes, 31 reducing oxidized ascorbate with its dehydroascorbate reductase activity, 32,33 and participation in the regulation of signal transduction. 34,35 Trx is a small 12-kDa protein, with two highly conserved vicinal cysteine residues (WCGPC) at the active site that can reduce protein-protein disulfides. 36 Oxidized Trx is then reduced by thioredoxin reductase (TR) with electrons donated from NADPH.…”
mentioning
confidence: 99%